Performance indicators of the top basketball players: Relations with several variables - Sindik, J. (Collegium Antropologicum, 2015)
The aim of this study was to determine the differences in performance indicators for top senior male basketball players, with respect to several independent variables: position in the team, total situation-related efficiency, age, playing experience and the time spent on the court within the game and during championship season. The final sample of participants was selected from all teams in A-1 Croatian men's basketball league. Significant differences have been found according to the players`: position in the team, total situation-related efficiency, and in interactions of the position in the team / total situation-related efficiency and minutes spent on the court in a game / playing experience. The differences in the situation-related efficiency between players have not been found according to the players` age and the number of games played. Further research can be directed towards deeper analysis of the influence of more complex differentiated variables playing experience and time spent on the court in a game on situation-related efficiency in basketball.